UJI PENAMBAHAN CANGKANG TELUR TERHADAP DAYA LEKAT CAT TEMBOK - Ivan Setia Arianto; Masturi Masturi; Ian Yulianti (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Chicken eggshell is a waste of underutilized when high calcium. Calcium content is also available in wall paint in this research will be tested against the adhesiveness with the addition of chicken eggshell. The independent variables in this research is a mixture of chicken egg shells and wall paint. The dependent variable is observed paint adhesiveness was observed with how big the tear paint when hung load. The control variables in the research was the temperature. Two sheets of paper HVS each coated with original paint and wall paint with a mixture of chicken egg shells. The second layer of HVS hung rope and load varied mass. The research was conducted by comparing how big the pieces of paper HVS coated mixture of chicken egg shells and wall paint with paper coated with original paint when suspended freely within 5 seconds. The results showed that the paper coated with a mixture of chicken egg shells and paint experiencing tear smaller than the paper original wall paint coated only with a load mass and the same time. The addition of chicken egg shells containing high calcium with wall paint produce adhesiveness paint better to make the paint into a durable and long lasting. Keywords: Chicken Egg Shell, wall paint, Adhesiveness.